Serum sCD40L levels are increased in patients with psoriatic arthritis and are associated with clinical response to apremilast. (27th May 2020) - Venerito, V; Natuzzi, D; Bizzoca, R; Lacarpia, N; Cacciapaglia, F; Lopalco, G; Iannone, F
Summary: The pathogenesis of psoriatic arthritis (PsA) involves several pathways, including the CD40/CD40L signaling which promotes the release of multiple cytokines. Transmembrane CD40L is also released in soluble form (sCD40L) and phosphodiesterase 4 (PDE4) seems to be involved in its cleavage. We aimed to investigate whether apremilast, a PDE4 inhibitor, could modify circulating levels of sCD40L in PsA patients, and the possible associations of these changes with clinical response. Consecutive PsA patients starting apremilast in routine clinical practice were prospectively observed. Disease Activity of Psoriatic Arthritis (DAPSA), Psoriasis Area Severity Index (PASI), Leeds Enthesitis Score (LEI) and serum samples were collected at baseline and at 6 months. Samples were run in a Bio-Plex ProTM plate for sCD40L. To investigate the association of sCD40L level with DAPSA based minor response, low disease activity (LDA) and/or remission at 6 months of treatment, multivariate logistic regression models with backward selection ( P < 0·05) were built. We studied 27 patients (16 of 27 women, 59·6%) with PsA and mean age [± standard deviation (s.d.)] of 58·4 ± 10 years. A significant reduction of the mean values of DAPSA, LEI and PASI was detected at 6 months. Mean serum levels of sCD40L decreased from baseline 5364 ± 2025 pg/ml to 4412 ± 2629 at 6 months ( P = 0·01). Baseline DAPSA [odds ratio (OR) = 0·80, 95% confidence interval (CI) = 0·65–0·98] and sCD40L (OR = 1·001, 95% CI = 1·0001–1·0027) were independently associated with DAPSA LDA/remission at 6 months. In PsA patients, sCD40L levels decrease upon apremilast treatment and might predict short-term clinical response to apremilast. Graphical Abstract: